2019
DOI: 10.1186/s12864-019-5811-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of selection signatures involved in performance traits in a paternal broiler line

Abstract: Background Natural and artificial selection leads to changes in certain regions of the genome resulting in selection signatures that can reveal genes associated with the selected traits. Selection signatures may be identified using different methodologies, of which some are based on detecting contiguous sequences of homozygous identical-by-descent haplotypes, called runs of homozygosity (ROH), or estimating fixation index (F ST ) of genomic windows that indicates genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 93 publications
4
22
1
2
Order By: Relevance
“…Studies have reported high correlation between F is and F ROH based on short ROH segments in cattle, suggesting ancestral inbreeding back up to 50 generations ago ( Ferenčaković et al 2013 ; Mastrangelo et al 2016 ; Limper 2018 ). The high correlation observed between two metrics of molecular inbreeding is consistent with the previous reports on chicken ( Bortoluzzi et al 2018 ; Marchesi et al 2018 ; Almeida et al 2019 ), cattle ( Ferenčaković et al 2013 ; Zhang et al 2015 ; Mastrangelo et al 2016 ; Peripolli et al 2018 ) and sheep ( Mastrangelo et al 2017 ; Purfield et al 2017 ; Mastrangelo et al 2018 ) as well as human model ( Clark et al 2019 ). These results confirm the usefulness of the ROH analysis in monitoring differentiation and inbreeding values for further exploitation in chicken breeding programs in the absence of pedigree records.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Studies have reported high correlation between F is and F ROH based on short ROH segments in cattle, suggesting ancestral inbreeding back up to 50 generations ago ( Ferenčaković et al 2013 ; Mastrangelo et al 2016 ; Limper 2018 ). The high correlation observed between two metrics of molecular inbreeding is consistent with the previous reports on chicken ( Bortoluzzi et al 2018 ; Marchesi et al 2018 ; Almeida et al 2019 ), cattle ( Ferenčaković et al 2013 ; Zhang et al 2015 ; Mastrangelo et al 2016 ; Peripolli et al 2018 ) and sheep ( Mastrangelo et al 2017 ; Purfield et al 2017 ; Mastrangelo et al 2018 ) as well as human model ( Clark et al 2019 ). These results confirm the usefulness of the ROH analysis in monitoring differentiation and inbreeding values for further exploitation in chicken breeding programs in the absence of pedigree records.…”
Section: Resultssupporting
confidence: 91%
“…The average size of ROH tracts observed in Red Junglefowls is comparable to the African indigenous chicken populations from Rwanda and Uganda both genotyped with the chicken Affymetrix 600K Axiom Array ( Elbeltagy et al 2019 ). Our measure of ROH in broiler populations confirms the dimension reported in previous studies ( Marchesi et al 2018 ; Almeida et al 2019 ). Layers, especially WL carry the lengthy ROH tracts with 432.1 Mb (± 18.7 Mb; max.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As selection is distinguished by local reductions in haplotype diversity, depending on the distribution of ROH patterns across the genome, results allow the identification of genomic regions that have been subjected to either recent and/or ancient selective pressure events [74,75]. These regions also allow, through gene ontology and enrichment analyses, identifying of candidate genes associated with selection for different traits, highlighting those of economic-interest in different livestock populations such as horses, cattle, sheep and poultry [76][77][78][79].…”
Section: Runs Of Homozygosity: Inbreeding Measurementmentioning
confidence: 99%